Российский рынок диссертационных услуг - КалимуллинТагир Равилович (Journal of Economic Sociology, 2010)
The beginning was published in 2005. Т. 6. № 4. The final part describes the main consumers of the ordered dissertations and types of writers. The paper deals with such questions as market entry, prices and ways of dissertation writing. The author underlines the problems of expertise for the dissertations and suggests the ways out of the problem of the dissertation services market.